If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13n + -11n = 14 Combine like terms: 13n + -11n = 2n 2n = 14 Solving 2n = 14 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Divide each side by '2'. n = 7 Simplifying n = 7
| -2x+5y+2=0 | | 3xa=5xa+40 | | 8r+4=8 | | 5(2x-8)-2(x+2)-16x= | | 6x-5y-12=0 | | 3x+y=-36 | | 4-x/x+2sqrtx | | 29/24-7/8 | | (y-x-1)dx+(x+y-1)dy=0I | | 7u-16u=0 | | -2,-8=1/2 | | (-2,_8);m=-1/2 | | 11x(13/19) | | (6x)(24)=72 | | 13/19=x/11 | | 103/7x101/2= | | 103/7*101/2 | | 14+5=25 | | 14+5=25 | | 103/7x101/2 | | 5x+200=2x+100 | | 17/12-(1/8 | | 8y^7-12y^5/2y^3= | | 4n-6=5-2n | | -9+n4=-7 | | 8y^7-12y^5/2y^3 | | (x/(x-3))+(4/x) | | (x/x-3)+(4/x) | | 6x^5-4x^3=-1 | | 3x+6y+5-y-9x-7= | | 5(x-5y)=0 | | (1/7)^(2x-5)=49 |